Review of engine journal bearing tribology in start-stop applications. (January 2020) - Santos, Nathália Duarte Souza Alvarenga; Roso, Vínicius Rückert; Faria, Marco Tulio C.
Highlights: Start-stop controls are used in internal combustion engines to reduce exhaust emissions and fuel consumption. This technology affects load, temperature variations, and lubricant delivery to key interfaces. This review focuses on the impact of start-stop operation on ICE bearing tribology. Abstract: The environmental impacts of the air pollution from motorized transportation in the public health has driven new environmental regulations to reduce the gas emission produced by combustion engines. To address this issue, the automotive industry has developed strategies to meet these new requirements, and the start-stop systems emerge as a promising technology to reduce exhaust emissions and fuel consumption. However, the start-stop systems lead to high loads on the main engine components, such as piston, piston rings and bearings, since the temperature variation and lubrication supply are intermittent with the frequent engine start up. Thereby, the present study aims at presenting a literature review of the tribological aspects of car start-stop systems. A discussion of the operating parameters associated with the engine tribological behavior, mainly focused on the bearing crankshaft, is the core of this study. The review encompasses the recent bearing developments to meet the new load requirements, as well as the latest bearing researches regarding friction, lubrication and wear.